Forest and labor in Madagascar : from colonial concession to global biosphere - Sodikoff, Genese Marie, 1966- (Indiana University Press, 2012)
Protecting the unique plants and animals that live on Madagascar while fueling economic growth has been a priority for the Malagasy state, international donors, and conservation NGOs since the late 1980s. Forest and Labor in Madagascar shows how poor rural workers who must make a living from the forest balance their needs with the desire of the state to earn foreign revenue from ecotourism and forest-based enterprises. Genese Marie Sodikoff examines how the appreciation and protection of Madagascar's biodiversity depend on manual labor. She exposes the moral dilemmas workers face as both co.